ATG Based Conditioning Regimen in Stem Cells Transplantation of Fanconi Anemia: A Single Center Experience of 63 Patients - Gamal M Fathy; Alaa El-Haddad; Hossam K Mahmoud; Omar Fahmy; Raafat Abdelfattah; Mohamed Abdel- Moot; Mahmoud Bokhary; Shaimaa Ibrahim (Annals of Bone Marrow Research - Peertechz Publications, 2017)
Introduction: Fanconi's anemia (FA) is a rare genetic disorder. Patients with this disorder have progressive bone marrow failure, congenital abnormalities and are vulnerable to malignancy. Aim: Explaining our single center experience regarding ATG based conditioning regimen that's used for the transplantation of patients with Fanconi's Anemia. Materials and methods: Sixty-three patients with Fanconi anemia (FA) underwent stem cells transplantation from matched siblings, either from peripheral blood (PBSCsT) in fifty nine patients , or bone marrow in four patients, according to donors' age and/weight. Mean age at BMT was 11.2 years. Conditioning regimen consisted of low-dose cyclophosphamide 5 mg/kg/d from d-5 to d-2 , fludarabin 120mg/m2 from d-10 to d-6, CSA: 3mg/ kg/d start from d -1 and Antithymocyte globulin (ATG) was added in the pre-transplant as well as the post-transplant period at a total dose of 30 mg/kg as follows: 5mg/kg/d (from d-4to d-1), 2.5mg/kg (d+1,d+3, d+6, d+11). We divided our patients into two cohorts based on age. The first cohort aged 12 years and older and the second cohort included patients younger than 12 years old. We also studied the overall survival according to the source of stem cells (Bone Marrow vs. Peripheral blood stem cells). Results: Engraftment has been achieved in 49 (77%) patients with a mean time of 13.2 days (range, 8-26 days) SD= 3.8. The mean time for a self-sustaining platelet count of > 25 ×109/l was 14.6 days (range, 8-30 days) SD= 4.5. Eight (12.7 %) patients developed acute GVHD; none developed extensive chronic GVHD, 4 Patients developed only limited chronic GVHD. Fourteen patients died before engraftment. Conclusion: Our current results underline the importance of using ATG in the conditioning regimen for the transplantation of patients with Fanconi's anemia.